(untitled) (Indonesian Journal of Agrarian Law, 2026)
The development of the risk-based business licensing system thru Online Single Submission (OSS-RBA) raises legal issues related to the relationship between administrative obligations and the validity of agreements in civil law. The main issue lies in whether the incompleteness or delay of permits can affect the validity of contracts that have been agreed upon by the parties. This research aims to analyze the position of permits in determining the validity of agreements and to formulate an ideal legal construction in harmonizing administrative law and civil law. The method used is normative legal research with a legislative and conceptual approach, supported by relevant doctrinal studies and legal theories. The research results indicate that the validity of the agreement still refers to Article 1320 of the Civil Code, where the aspect of licensing is not included as a condition for the validity of the agreement as long as the causa does not contravene the law. The failure to obtain permits is more accurately categorized as an administrative violation. Furthermore, obstacles in the OSS system can be classified as a form of relative force majeure that affects the performance of obligations, but does not nullify the validity of the contract. The contribution of this research lies in strengthening the argument regarding the separation and simultaneous interconnection between public and private law in contractual practice. This research concludes that an integrative legal reconstruction is necessary, balancing legal certainty, justice, and utility.